An industrial assessment for a multimodel framework. Issue 9 (22nd August 2014) - Larrucea, Xabier; Santamaria, Izaskun; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT Software process improvement (SPI) initiatives are facing complex environments where stakeholders need to integrate different reference models in their organizations. There are several approaches to multimodel environments defining some steps or activities that should be carried out for implementing it efficiently inside organizations. This paper presents a report on the use of a multimodel framework integrating three quality reference models in 47 SPI initiatives. Basically, this report is based on statistical data extracted from industrial assessments. Copyright © 2014 John Wiley & Sons, Ltd.